Application of Light-Sheet Mesoscopy to Image Host-Pathogen Interactions in Intact Organs - Battistella, Eliana; Quintana, Juan F.; McConnell, Gail (Frontiers in Cellular and Infection Microbiology, 2022)
Human African Trypanosomiasis (HAT) is a disease caused by the extracellular parasite Trypanosoma brucei that affects the central nervous system (CNS) during the chronic stage of the infection, inducing neuroinflammation, coma, and death if left untreated. However, little is known about the structural change happening in the brain as result of the infection. So far, infection-induced neuroinflammation has been observed with conventional methods, such as immunohistochemistry, electron microscopy, and 2-photon microscopy only in small portions of the brain, which may not be representative of the disease. In this paper, we have used a newly-developed light-sheet illuminator to image the level of neuroinflammation in chronically infected mice and compared it to naïve controls. This system was developed for imaging in combination with the Mesolens objective lens, providing fast sub-cellular resolution for tens of mm3-large imaging volumes. The mouse brain specimens were cleared using CUBIC+, followed by antibody staining to locate Glial Fibrillary Acid Protein (GFAP) expressing cells, primarily astrocytes and ependymocytes, used here as a proxy for cell reactivity and gliosis. The large capture volume allowed us to detect GFAP+ cells and spatially resolve the response to T. brucei infection. Based on morphometric analyses and spatial distribution of GFAP+ cells, our data demonstrates a significant increase in cell dendrite branching around the lateral ventricle, as well as dorsal and ventral third ventricles, that are negatively correlated with the branch extension in distal sites from the circumventricular spaces. To our knowledge, this is the first report highlighting the potential of light-sheet mesoscopy to characterise the inflammatory responses of the mouse brain to parasitic infection at the cellular level in intact cleared organs, opening new avenues for the development of new mesoscale imaging techniques for the study of host-pathogen interactions.